PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP INDEKS PEMBANGUNAN MANUSIA PADA KAB./KOTA PROPINSI SUMATERA UTARA - Riva Ubar Harahap (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
The purpose of this study is to identify and analyze whether General Allocation Fund (DAU), Special Allocation Fund (DAK) and Profit Sharing Fund (DBH) influence simultaneously and partially to Human Development Index (IPM). The analytical method used is multiple regressions by doing classic assumption test method prior to gather the best model research. These variabel research such as the General Allocation Fund, Special Allocation Fund and Profit Sharing Fund are independent variables and Human Development Index is dependent variable. Research sample is 25 district/city in North Sumatera Province. DAU, DAK and DBH obtained from www.djpkd.depkeu.go.id. The data of Human Development Index obtained from Indonesia Statistics Centre Institution.The results of this study concluded that the General Allocation Fund, Special Allocation Fund and Profit Sharing Fund influence simultaneously to the Human Development Index. The result consistent with research hypothesis. General Allocation Fund, Special Allocation Fund and Profit Sharing Fund have no effect partially to the Human Development Index. The result consistent with research hypothesis.